Data Privacy: Foundations, New Developments and the Big Data Challenge - Torra, Vicenç; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book offers a broad, cohesive overview of the field of data privacy. It discusses, from a technological perspective, the problems and solutions of the three main communities working on data privacy: statistical disclosure control (those with a statistical background), privacy-preserving data mining (those working with data bases and data mining), and privacy-enhancing technologies (those involved in communications and security) communities. Presenting different approaches, the book describes alternative privacy models and disclosure risk measures as well as data protection procedures for respondent, holder and user privacy. It also discusses specific data privacy problems and solutions for readers who need to deal with big data.
Introduction -- Machine and Statistical Learning -- On the Classiﬁcation of Protection Procedures -- User's privacy -- Privacy Models and Disclosure Risk Measures -- Masking methods -- Information loss: evaluation and measures -- Selection of masking methods -- Conclusions.
Keywords: Computational intelligence; Artificial intelligence; Computational Intelligence; Artificial Intelligence